Efektivitas, Efisiensi Dan Kesehatan Hubungan Organisasi Pelayanan Dalam Kepemimpinan Kristen - Marde Christian Stenly Mawikere (Sekolah Tinggi Teologi Simpson, 2018)
Marde Christian Stenly Mawikere, Effectiveness, Efficiency And Health Relationships Service Organization In Christian Leadership. This article reviews the importance of Christian leadership in service organizations. It highlights the aspects that shape and support the effectiveness, efficiency and health of organizational relationships in Christian Leadership. This article emphasizes that in Christian Leadership it begins on the basis of the decision of God's sovereign grace. A Christian leader is a chosen person based on God's own initiative. In the dictionary (leadership) of Christianity, nothing is